Enhancing soil carbon sequestration with plant residue quality and soil management - White, Paul Mark Jr. (Kansas State University, 2006)
Atmospheric concentrations of the greenhouse gases (GHG) carbon dioxide (CO2), nitrous oxide, and methane have been increasing since the Industrial Revolution. An expanding human population, increased fossil fuel use, extensive ecosystem disturbance, and intensive production agriculture have contributed to this increase. Storing carbon (C) in soil in natural and agricultural ecosystems has the potential to offset a portion of the future atmospheric increases in CO2 levels. Laboratory and field studies were conducted to evaluate basic mechanisms of C sequestration. The research reported here focuses on identifying strategies to reduce C loss from soil by (1) slowing plant residue decomposition rates, or (2) increasing soil fungal dominance and physical protection of soil C. Grain sorghum (Sorghum bicolor) hybrids were used in a laboratory experiment to determine the effect of varied amounts of lignin on plant residue C mineralization. The different levels of lignin in the hybrids was not strongly correlated with plant residue C mineralization. Another laboratory experiment investigated larger differences in lignin content between crop plants. Plant residue exhibiting the natural mutation referred to as brown midrib (bmr) also had lowered total lignin and different lignin chemistry. The bmr plants decomposed faster than the normal isolines, and the addition of nitrogen lowered overall mineralization. Nitrogen additions also significantly impacted the microbial community by lowering total phospholipid fatty acids (PLFA) and shifting fungal energy storage physiology. A field experiment was conducted to measure the soil microbial response to adding grain sorghum residue in both tillage (CT) and no-tillage (NT) agricultural ecosystems. The residue mineralized similarly in both systems, but the NT microbial population was stimulated significantly greater than CT. The fungal PLFA in NT 0-5 cm was higher than NT 5-15 cm, CT 0-5 cm, or CT 5-15 cm. A significantly greater amount of plant residue C was found in soil macroaggregates, as compared to microaggregates, at the conclusion of the experiment, regardless of tillage. More N was found in NT macroaggregates than in CT macroaggregates. The experiment identified two mechanisms for increased C storage in NT soils, as compared to CT soils.
Keywords: Soil; Carbon Sequestration; Microbial; Ecology; Climate; Agriculture, Agronomy (0285)